Unusual occurrence of brain hydatid disease in a patient with previous surgical intervention for hemorrhagic venous infarct (Indian Journal of Case Reports, 2018)
Hydatid disease is an endemic parasitic disease and can occur anywhere in the body and has a variable presentation. On imaging, the lesions have varied appearance ranging from cystic to solid appearing lesions, solitary to multiples. We present a case of 35-year-old female who underwent decompression craniectomy for right temporoparietal hemorrhagic venous infarct and now presented with acute onset of right-sided weakness. Magnetic resonance imaging was suggestive of cerebral hydatid disease. The presented case emphasizes that hydatid cyst should be considered as a possibility whenever a cystic lesion is encountered during imaging.